2006
DOI: 10.1056/nejmicm031071
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Metastases of Small-Cell Lung Cancer

Abstract: images in clinical medicineT h e ne w e ngl a nd jou r na l o f m e dic i ne n engl j med 354;24 www.nejm.org june 15, 2006 2583A 70-year-old former smoker presented with a history of several weeks of multiple painless cutaneous nodules on his chest wall. He also reported fatigue, weight loss, and cough with blood-tinged sputum. More than 30 subcutaneous nodules were identified on physical examination (Panel A). There was no clubbing, peripheral edema, or joint deformity. The respiratory examination was otherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…It has been reported that metastatic skin lesions spread either via lymphatic or hematogenous route. It is not very common to detect skin metastases in patients with small cell lung cancer, however when it presents a poorer prognosis is expected [16][17][18]. Consequently, histopathological confirmation with biopsy should be performed for suspicious skin or subcutaneous lesions to distinguish metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that metastatic skin lesions spread either via lymphatic or hematogenous route. It is not very common to detect skin metastases in patients with small cell lung cancer, however when it presents a poorer prognosis is expected [16][17][18]. Consequently, histopathological confirmation with biopsy should be performed for suspicious skin or subcutaneous lesions to distinguish metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, facial metastases occurred during chemotherapy. Metastases in skin occur when the disease has progressed and are indicator of poor prognosis and short survival [ 2 , 6 , 13 ]. There are reports that the survival time after the appearance of skin metastases is about 5-6 months [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other internal malignancies, lung cancer is the fastest in developing skin metastases after initial diagnosis [ 12 ]. The occurrence of cutaneous metastases from lung cancer is a poor prognostic indicator [ 13 ]. Coexistence of skin metastases with other extracutaneous metastases decreases the average survival time to approximately three months [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Кожните метастази от белодробен карцином са рядкост [3][4]. Появата им е признак на авансирало заболяване и е предиктор за ниска преживяемост [5][6]. Данните показват, че след проявата на кожни метастази, продължителността на живота е до 6 месеца [3].…”
Section: обсъжданеunclassified